2021
DOI: 10.3389/fpsyt.2021.654589
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Online Home-Based Treatment During the COVID-19 Pandemic for Ultra-Orthodox Young Women With Eating Disorders

Abstract: Background: With the outbreak of the COVID-19 pandemic, the need arose to maintain treatment continuity for religious Jewish Ultra-Orthodox young women with eating disorders (EDs) previously hospitalized in the ED department at the Ultra-Orthodox “Mayanei Hayeshua” medical center in Israel. This need led to the development of home-based online treatment channels, previously unfamiliar, and unaccepted in this population. The implementation of this model had to take into consideration many of the difficulties in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…Considering additional familial views, a recent case study [ 26 ] involving three young women with eating disorders who received a virtual, home-based treatment model of care found perceptions of virtual treatment similar to our study. For example, some patients and families found the online intervention acceptable and assisted in improving their behaviours, but others noted several challenges that acted as barriers to effectiveness, such as feeling anxious and uncomfortable disclosing sensitive information online [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Considering additional familial views, a recent case study [ 26 ] involving three young women with eating disorders who received a virtual, home-based treatment model of care found perceptions of virtual treatment similar to our study. For example, some patients and families found the online intervention acceptable and assisted in improving their behaviours, but others noted several challenges that acted as barriers to effectiveness, such as feeling anxious and uncomfortable disclosing sensitive information online [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
“…Considering additional familial views, a recent case study [ 26 ] involving three young women with eating disorders who received a virtual, home-based treatment model of care found perceptions of virtual treatment similar to our study. For example, some patients and families found the online intervention acceptable and assisted in improving their behaviours, but others noted several challenges that acted as barriers to effectiveness, such as feeling anxious and uncomfortable disclosing sensitive information online [ 26 ]. More generally, systematic review results related to patient views of virtual mental health care indicate patient satisfaction with psychotherapeutic interventions and therapeutic alliance that is comparable to in-person delivery [ 27 ]; however this review does not contain findings from the COVID-19 era, which might also have influenced some experiences with virtual care during our study.…”
Section: Discussionsupporting
confidence: 83%
“…The Maudsley Centre for Child and Adolescent Eating Disorders, which transitioned to online treatment delivery during COVID-19, found that parents ( n = 19) generally felt more comfortable than young people ( n = 14) in online groups and they tended to feel more positive about the online format overall [ 51 ]. In Israel, home-based online treatment during the pandemic brought mixed experiences, including patients’ reluctance to take part, a lack of access to technological devices, the impact of family and religious circumstances, whilst conversely, the virtual option was more positive for some patients and their parents [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study's participants with eating disorders reported the opposite: they reported greater comfort and perceived efficiency of remote therapeutic services. Since the start of the COVID-19 pandemic, a number of studies have explored the initial effects of widespread moves to telehealth for patients with eating disorders and have shown mixed results [46][47][48][49][50]. Treatment modalities on line can lead to greater disinhibition and openness among avoidant personalities [51,52] because of their greater sense of safety.…”
Section: Discussionmentioning
confidence: 99%